Multicentre evaluation of an antigen-detection ELISA for the diagnosis of Trypanosoma brucei rhodesiense sleeping sickness. - Komba, E. (World Health Organization, 1992)
The performance of an enzyme-linked immunosorbent assay (antigen ELISA) for the detection, in serum or cerebrospinal fluid, of an invariant trypanosome antigen to diagnose Trypanosoma brucei rhodesiense sleeping sickness was evaluated in four clinical treatment centres. The test, which was carried out in polystyrene test-tubes, was positive in 88 (88.9%) of 99 parasitologically confirmed cases that were tested at the National Institute for Medical Research, Tabora, United Republic of Tanzania; 99 (94.3%) of 105 cases tested at the National Sleeping Sickness Control Programme, Jinja, Uganda; 86 (87.8%) of 98 cases tested at the Uganda Trypanosomiasis Research Organisation, Tororo, Uganda; and 59 (96.7%) of 61 cases tested at the Tropical Diseases Research Centre, Ndola, Zambia. The overall detection rate was 91.5%. There was no cross-reactivity with the agents of the common bacterial, viral, or parasitic diseases prevalent in the areas where the studies were conducted. The only false-positive result involved a blood donor from a trypanosomiasis endemic focus. The test was simple to perform, was read visually, and is therefore a potential tool for diagnosing human African trypanosomiasis.